Interplay between host non-coding RNAs and influenza viruses. Issue 5 (4th May 2021) - Bamunuarachchi, Gayan; Pushparaj, Samuel; Liu, Lin
ABSTRACT: Influenza virus infection through seasonal epidemics and occasional pandemics has been a major public health concern for decades. Incomplete protection from vaccination and increased antiviral resistance due to frequent mutations of influenza viruses have led to a continuous need for new therapeutic options. The functional significance of host protein and influenza virus interactions has been established, but relatively less is known about the interaction of host noncoding RNAs, including microRNAs and long noncoding RNAs, with influenza viruses. In this review, we summarize host noncoding RNA profiles during influenza virus infection and the regulation of influenza virus infection by host noncoding RNAs. Influenza viral non-coding RNAs are briefly discussed. Increased understanding of the molecular regulation of influenza viral replication will be beneficial in identifying potential therapeutic targets against the influenza virus.